2019
DOI: 10.13057/biodiv/d200507
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and inheritance in cowpea (Vigna unguiculata) on protein and yield components characters

Abstract: Abstract. Purnamasari I, Sobir, Syukur M. 2019. Diversity and inheritance in cowpea (Vigna unguiculata) on protein and yield components characters. Biodiversitas 20: 1294-1298.  Diallel was a method that can be used to see inheritance and diversity character of plants. The objective of this study has evaluated the inheritance and diversity of the yield component characters and seed protein content. This study used genetic material from five homozygous cowpeas (Vigna unguiculata (L.) Walp) genotypes (KM1, KM2, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 15 publications
1
17
0
Order By: Relevance
“…Likewise, the fact that the (H/D) 1/2 ratio is greater than 1 in the F2 generation indicates superior dominance and supports this result. Magar et al (2016), Gupta et al (2017), Kumari and Chauhan (2018), and Purnamasari et al (2019) agreed with these results. Hall et al (2003), andVerma et al (2020) stated that additive genes were effective on the number of pods in the plant.…”
Section: Number Of Podssupporting
confidence: 53%
See 1 more Smart Citation
“…Likewise, the fact that the (H/D) 1/2 ratio is greater than 1 in the F2 generation indicates superior dominance and supports this result. Magar et al (2016), Gupta et al (2017), Kumari and Chauhan (2018), and Purnamasari et al (2019) agreed with these results. Hall et al (2003), andVerma et al (2020) stated that additive genes were effective on the number of pods in the plant.…”
Section: Number Of Podssupporting
confidence: 53%
“…In the study, it was revealed that the heritability in the broad sense was large and the heritability in the narrow sense was low, and the number of pods was also affected by the environment. Working on similar issues, Purnamasari et al (2019), andOwusu et al (2020) found high heritability broad and narrow sense. It can be argued that it would be better to start breeding after 3-4 generations, since non-additive genetic effects are important in the generation examined.…”
Section: Number Of Podsmentioning
confidence: 99%
“…The hybridization process was carried out to combine characters from two genetically different parents. According to Purnamasari et al (2019), the characteristics of yield components inherited additively in cowpea include the number of seeds per pod, number of pods per plant, length of young pods, and length of old pods, yield per plant, and protein content of seeds. The inheritance pattern in the characters controlled by these additive genes causes genotypes that have the same characteristics as their superior parents or even superior to their parents.…”
Section: Discussionmentioning
confidence: 99%
“…The level of individual phenolic compounds depends on the variety rather than on the phenotype (Ojwang 2012). Characters that are influenced by additive gene action and have high diversity allow them to be selected in the F2 generation using the genealogical selection method (Purnamasari 2019).…”
Section: The Quantitative Charactermentioning
confidence: 99%